An Exposition of Research Methodology in Management and Social Sciences - Sadri, Sorab (Journal of Economic Development, Environment and People, 2013)
In writing this paper the author has consciously stood apart from his earlier works and attempted to dispassionately review his own position so that some degree of clarity of thought might emerge in the process. The paper is based on the author’s contribution between 1992 and 2012 to this subject and which has been used as the basis for several doctoral level investigations under the author’s guidance. They had played a major role in helping the author to crystallize his views. To these scholars, therefore, the author’s gratitude is unflinchingly extended. Management has been described as being concerned with and based on the science of decision making and operating from the foundations of the art of decision executing. Hence, research in the area of modern Human Resources Management, especially, is both interesting and challenging having its one foot planted in industrial sociology and industrial psychology while the other placed in supply chain management and organisational restructuring. Hence, the argument of this paper is more relevant to serious research scholars and to those management teachers who wish to pursue rigorous academic research. This is not meant for those in the cut-copy-paste league, which unfortunately is, of late, becoming quite prevalent within the Indian academia.